Effect of Bilvapatra Lepa (Aegle Marmelos) over unknown insect bite Poisoning - A Single Case Study (International Journal of Scientific Research in Science and Technology, 2024)
Ayurveda is the ancient science of life, has eight branches. According to Ayurved there are two main types of poison – Natural and Artificial. Natural poison is of two types – Sthavar and Jangam. (1) Danstrachikita is a Ayurveda toxicology branch. Insect bite is comes under Jangam Visha. A 9 year boy, while playing cricket affect with unknown insect bite complying of itching, swelling, redness and burning pain over upper back region. He was treated by local application of Bilvapatra Lepa (Aegle marmelos). Aegle marmelos is one of the important plants which have medicinal as well as other properties. This study shows that external application of Bilvapatra Lepa is effective in the treatment of unknown insect bite (Kitakadansha)